Teaching Medicine Online During The Covid-19 Pandemic: A Malaysian Perspective - Aneesa Abdul Rashid; Mohd Radzniwan A Rashid; Mohamad Nurman Yaman; Irfan Mohamad (Bangladesh Journal of Medical Science, 2024)
Volume: 19 'Special issue on Covid 19' 2020